2002
DOI: 10.1128/aem.68.1.263-270.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the Gene Cluster Involved in Chitin Degradation in a Marine Bacterium, Alteromonas sp. Strain O-7

Abstract: Alteromonas sp. strain O-7 secretes chitinase A (ChiA), chitinase B (ChiB), and chitinase C (ChiC) in the presence of chitin. A gene cluster involved in the chitinolytic system of the strain was cloned and sequenced upstream of and including the chiA gene. The gene cluster consisted of three different open reading frames organized in the order chiD, cbp1, and chiA. The chiD, cbp1, and chiA genes were closely linked and transcribed in the same direction. Sequence analysis indicated that Cbp1 (475 amino acids) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 39 publications
(35 reference statements)
1
39
0
Order By: Relevance
“…O-7 chiD, cbp1 and chiA (Genbank accession no. AB063629; Tsujibo et al, 2002) genes are also arranged in this order in a cluster, and the domains identified within each gene are similarly located in S91 chiABC ( Figure 1 and Table 5; Techkarnjanaruk and Goodman, 1999). The GC content of each gene cluster is similar (46% for S91 and 45% for O-7).…”
Section: Discussionmentioning
confidence: 85%
“…O-7 chiD, cbp1 and chiA (Genbank accession no. AB063629; Tsujibo et al, 2002) genes are also arranged in this order in a cluster, and the domains identified within each gene are similarly located in S91 chiABC ( Figure 1 and Table 5; Techkarnjanaruk and Goodman, 1999). The GC content of each gene cluster is similar (46% for S91 and 45% for O-7).…”
Section: Discussionmentioning
confidence: 85%
“…13,[24][25][26] On the other hand, NAGs have been reported to be located in periplasmic space or in cytoplasm in the case of marine bacteria. 22,23,27) This intracellular localization of enzymes appears to be advantageous for an efficient hydrolysis of chitin in sea water, since hydrolyzed products can easily be taken into cells. The existence of a signal peptide in a precursor peptide of NAG20A suggests that NAG20A can be exported across the cellular membrane.…”
Section: Discussionmentioning
confidence: 99%
“…A chitinolytic enzyme system has not been clarified so far for bacteria living in fresh water, although a detailed characterization has been reported for marine bacteria, such as Altermonas sp. O-7 22) and All sequences corresponded to the domain III regions (residues 336-818) of S. marcescens chitobiase, which contains catalytic center residues. Numerals show the number of amino acid residues initiated from the N-terminus of the total ORF.…”
Section: Discussionmentioning
confidence: 99%
“…Chitinases hydrolyze chitin to soluble oligosaccharides, mainly chitobiose, which are further hydrolyzed to GlcNAc by GlcNAcases which is then taken up by the cells as a carbon and nitrogen source 5 . Chitinases are produced by a number of microorganisms such as Bacillus, Pseudomonas, Serratia, Stenotrophomonas, Streptomyces and Vibrio; and is one of the mechanism that has been implicated in biocontrol of fungal diseases 6 .…”
Section: Introductionmentioning
confidence: 99%